ACVR2B antagonism as a countermeasure to multi‐organ perturbations in metastatic colorectal cancer cachexia. Issue 6 (16th November 2020) - Huot, Joshua R.; Pin, Fabrizio; Narasimhan, Ashok; Novinger, Leah J.; Keith, Austin S.; Zimmers, Teresa A.; Willis, Monte S.; Bonetto, Andrea
Abstract: Background: Advanced colorectal cancer (CRC) is often accompanied by the development of liver metastases, as well as cachexia, a multi‐organ co‐morbidity primarily affecting skeletal (SKM) and cardiac muscles. Activin receptor type 2B (ACVR2B) signalling is known to cause SKM wasting, and its inhibition restores SKM mass and prolongs survival in cancer. Using a recently generated mouse model, here we tested whether ACVR2B blockade could preserve multiple organs, including skeletal and cardiac muscle, in the presence of metastatic CRC. Methods: NSG male mice (8 weeks old) were injected intrasplenically with HCT116 human CRC cells (mHCT116), while sham‐operated animals received saline ( n = 5–10 per group). Sham and tumour‐bearing mice received weekly injections of ACVR2B/Fc, a synthetic peptide inhibitor of ACVR2B. Results: mHCT116 hosts displayed losses in fat mass ( − 79%, P < 0.0001), bone mass ( − 39%, P < 0.05), and SKM mass (quadriceps: − 22%, P < 0.001), in line with reduced muscle cross‐sectional area ( − 24%, P < 0.01) and plantarflexion force ( − 28%, P < 0.05). Further, despite only moderately affected heart size, cardiac function was significantly impaired (ejection fraction %: − 16%, P < 0.0001; fractional shortening %: − 25%, P < 0.0001) in the mHCT116 hosts. Conversely, ACVR2B/Fc preserved fat mass ( + 238%, P < 0.001), bone mass ( + 124%, P < 0.0001), SKM mass (quadriceps: + 31%, P < 0.0001), size (cross‐sectional area: + 43%, P < 0.0001) and plantarflexion force ( + 28%, P < 0.05) in tumour hosts. Cardiac function was also completely preserved in tumour hosts receiving ACVR2B/Fc (ejection fraction %: + 19%, P < 0.0001), despite no effect on heart size. RNA sequencing analysis of heart muscle revealed rescue of genes related to cardiac development and contraction in tumour hosts treated with ACVR2B/Fc. Conclusions: Our metastatic CRC model recapitulates the multi‐systemic derangements of cachexia by displaying loss of fat, bone, and SKM along with decreased muscle strength in mHCT116 hosts. Additionally, with evidence of severe cardiac dysfunction, our data support the development of cardiac cachexia in the occurrence of metastatic CRC. Notably, ACVR2B antagonism preserved adipose tissue, bone, and SKM, whereas muscle and cardiac functions were completely maintained upon treatment. Altogether, our observations implicate ACVR2B signalling in the development of multi‐organ perturbations in metastatic CRC and further dictate that ACVR2B represents a promising therapeutic target to preserve body composition and functionality in cancer cachexia.